2017
DOI: 10.1016/j.jfludis.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the mechanisms of change following an integrated group intervention for stuttering, as perceived by school-aged children who stutter (CWS)

Abstract: The reader will be able to (1) describe the integrated intervention used in this study (2) define the most significant change following therapy for the participants involved (3) summarise the key factors that facilitated change during the therapy process (as perceived by the participants).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Although the relationship between the working alliance and treatment outcomes has received consistent support across studies within psychotherapy (Del Re et al 2012, Flückiger et al 2018, Wampold 2015, the literature regarding the role of the working alliance within speech and language therapy (SLT) is relatively limited to date (Bright et al 2011, Caughter and Dunsmuir 2017, Fourie 2009, Lawton et al 2018a, 2018b. As with the field of physiotherapy McPherson 2012, Miciak et al 2018), SLT has borrowed theory from psychotherapy to inform the research and practice.…”
Section: The Concept Of the Working Alliancementioning
confidence: 99%
See 1 more Smart Citation
“…Although the relationship between the working alliance and treatment outcomes has received consistent support across studies within psychotherapy (Del Re et al 2012, Flückiger et al 2018, Wampold 2015, the literature regarding the role of the working alliance within speech and language therapy (SLT) is relatively limited to date (Bright et al 2011, Caughter and Dunsmuir 2017, Fourie 2009, Lawton et al 2018a, 2018b. As with the field of physiotherapy McPherson 2012, Miciak et al 2018), SLT has borrowed theory from psychotherapy to inform the research and practice.…”
Section: The Concept Of the Working Alliancementioning
confidence: 99%
“…, Wampold ), the literature regarding the role of the working alliance within speech and language therapy (SLT) is relatively limited to date (Bright et al . , Caughter and Dunsmuir , Fourie , Lawton et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the teacher supports the student to access skills through the use of visual cues (e.g., hand gesture or a symbol placed on the student's desk). The addition of a once-per-week, 30-min small group session with the SLP provides an opportunity for Paul to experience the support of peers while building skills (Caughter & Dunsmuir, 2017;Fry et al, 2014;Liddle et al, 2011). The role of the family can be crucial in supporting the child, and as such, it is important to support the parents in managing their own emotional reactions to their child's stuttering (Berquez & Kelman, 2018).…”
Section: Integrated Interventionmentioning
confidence: 99%
“…So, my dilemma is, if you do not "learn" to stutter, how does a behavioral contingency program work to successfully obliterate the disorder? Many have suggested that common factors, such as therapeutic alliance (Caughter & Dunsmuir, 2017), encouragement of self-efficacy in the parents who stutter and their children, and even the planned and graduated imposition of language challenge built into the parent-child interactions in LP (Bernstein Ratner & Guitar, 2006;Hayhow, 2011), could be responsible for children's improvement. Certainly, that would explain the RESTART findings of no detectable difference between success rates of children receiving LP and DCM therapies.…”
Section: Mechanism Of Actionmentioning
confidence: 99%